Perencanaan Perkerasan Jalan dengan Metode Manual Desain Perkerasan (MDP) (Studi Kasus: Jalan Poncowati – Purnama Tunggal Kabupaten Lampung Tengah) - Krisnanda, Rico; Wisman, Mira; Oktarina, Devi (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Increasing population leads to increased access needs roads as a means to move from a place. It takes a path feasible so that there are no obstacles that occur, it is expected to do road planning using pavement design Manual method (MDP) 2017 to get a design that is in accordance with its designation. This research done with the aim of knowing the existing condition of the road and determine design optimal pavement planning to fit the existing conditions on the road Poncowati-Purnama Tunggal Lampung Tengah Regency because on the road there are many public facilities needed people and road conditions are quite damaged. Research methods by means of calculate the volume of vehicle traffic and require primary data in the form of survey results of existing road conditions, and soil bearing capacity by using (Dynamic Cone Penetrometer) DCP. Secondary Data used is data (Average daily traffic) LHR. The results obtained carrying capacity conditions the soil is quite good with the smallest CBR results of 20.03 so it does not need improvement of subgrade condition on Poncowati-Purnama Tunggal road. Road conditions have been damaged and need to be repaired by using flexible pavement based on ESA calculation results Rank 4 and pavement design selection table in pavement design Manual (MDP) 2017, with the thickness of the upper foundation layer (LFA) 400 mm, Asphaltic Concrete Binder Course (AC-BC) 60 mm, and asphalt Concrete Wearing Course (AC-WC) 40 mm based on the calculation of ESA Power 5 and using reference to the design table in the pavement design Manual (MDP) 2017. There is a repair of total damage (reconstruction). Budget plan (RAB) wich estimate at Rp.9.291.416.000,-